Natural infection of cortelezzii complex (Diptera: Psychodidae: Phlebotominae) with Leishmania braziliensis in Chaco, Argentina - Rosa, Juan Ramón (2012)
In Argentina, American Cutaneous Leishmaniasis (ACL) extends up to 29°S in the phytogeographic regions of the Yungas (west), Chaco (center) and Paranaense (east). Since the Phlebotominae vectors of this disease in the western Chaco (dry Chaco) are unknown, in the present work, we studied the natural infection in Phlebotominae by PCR-ERFLP and Dot blot in order to incriminate these organisms as potential vectors. Captures with CDC-type traps were performed monthly in the domicile, the peridomicile and the forest in the Municipio Misión Nueva Pompeya, Chaco, Argentina, in two sites with human cases of ACL: Los Pozos (24°54′S, 61°22′W) and Fortín Arenales (24°58′S, 61°21′W), from November 2006 to December 2007. A total of 1702 Phlebotominae were captured: Mygonemyia migonei (83.8%), cortelezzii complex (11.1%), Mycropigomyia peresi (3.3%), Mycropygomy quinquefer (1.2%), Pintomyia torresi (0.2%) and Nyssomyia neivai (0.2%). Although no significant differences were found in species diversity, there were significant differences in abundance between both sites studied. A total of 80 phlebotomine females were analyzed: 50 of the cortelezzii complex and 30 My. migonei. No intestinal flagellates were observed by light microscopy. Two pools of 10 individuals of the cortelezzii complex of the peridomicile and forest of Fortín Arenales were reactive by PCR and Dot blot for Leishmania (Viannia) braziliensis. In Argentina, Evandromyia cortelezzii has been incriminated as a likely vector of ACL because of its abundance in areas of sporadic outbreaks. In the present work, Ev. cortelezzii females were found naturally infected, thus reinforcing the hypothesis that the members of the cortelezzii complex act as vectors of the disease.